Reduction of Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) Levels in Rubber Wastewater Using Biosand Filter Reactor with Activated Carbon Media Based on the Effect of Residence Time - Lisbet Farida Sinaga; Andika Munandar; Rifka Noor Azizah (Journal of Community Based Environmental Engineering and Management, 2023)
Wastewater from the rubber industry that is not treated optimally can be one of the causes of environmental damage. Initial concentration of COD waste rubber liquid 711 mg/l and TSS 407 mg / l. Biosand Filter with activated carbon can eliminate pathogenic bacteria by passing the sand in the filter and activated carbon will absorb organic substances. This study aims to determine the effectiveness of concentration reduction, COD and TSS, using a reactor with BioSand Filter reactor dimensions used measuring 12 cm x 12 cm x 120 cm and its effect on residence time. Filter Media used are sand, gravel, pumice and activated carbon. The research variable is the residence time in the reactor (10, 30, 50, 70, and 90 minutes). Removal efficiency after being processed using Biosand Filter technology with activated carbon media lowered the concentration of COD and TSS parameters to 93% for COD and 79% for TSS. Test the effect of residence time to reduce the levels of COD and TSS is done by regression test has a value of R2=0.7014 for COD and R2=0.681 for TSS, with tcount > ttable. the results show that the residence time of rubber wastewater in the reactor affect the decrease levels of COD and TSS, and quite effective in eliminating COD and TSS parameters.